2008
DOI: 10.1007/s00467-008-0781-6
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab treatment of collapsing C1q glomerulopathy: clinical and histopathological evolution

Abstract: A 13-year-old girl with obesity and hyperinsulinism developed steroid-resistant nephrotic syndrome due to collapsing glomerulopathy with dominant C1q-containing mesangial immune deposits (CG/C1qN). She became overtly diabetic while receiving alternate-day prednisone and tacrolimus, requiring insulin injections. Despite the addition of mycophenolate mofetil to the treatment regimen, renal function subsequently declined. Rituximab (four weekly doses of 375 mg/m 2 ) was tried 6 months after initial presentation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Sinha et al reported a case of steroid dependent C1qN in an 11 year old boy who was treated successfully with rituximab (375 mg/m 2 weekly for 4 weeks) . The mechanism of beneficial effect of this agent remains unclear but could be related to inhibition of production of pathological immunoglobulins that bind C1q or binding to B cells in tubulointerstial/ mesangial infiltrates . This case also suggests the promise in titrating rituximab to CD‐19 levels rather than going by fixed dosage schedules …”
mentioning
confidence: 94%
“…Sinha et al reported a case of steroid dependent C1qN in an 11 year old boy who was treated successfully with rituximab (375 mg/m 2 weekly for 4 weeks) . The mechanism of beneficial effect of this agent remains unclear but could be related to inhibition of production of pathological immunoglobulins that bind C1q or binding to B cells in tubulointerstial/ mesangial infiltrates . This case also suggests the promise in titrating rituximab to CD‐19 levels rather than going by fixed dosage schedules …”
mentioning
confidence: 94%
“…While there are no reports of the successful use of rituximab in the management of C1qN, it is conceivable that B-cell depletion may reduce pathogenic C1q activation by decreasing antibody and new immune complex formation [7]. Here, we report two patients with symptomatic C1qN where dramatic improvement in clinical symptoms and biochemical parameters were seen following rituximab therapy.…”
Section: Introductionmentioning
confidence: 71%
“…The decision to use rituximab in our patients was taken after conventional options were exhausted. To our knowledge rituximab treatment for C1qN has been reported only once [7]. A 13-year-old girl showed initial improvement following treatment with rituximab; however, repeat administration 20 months later failed to impact the disease course, possibly due to marked chronic glomerular damage that was not reversible with B-cell depletion.…”
Section: Discussionmentioning
confidence: 93%
“…Since the first report of C1q nephropathy by Jennette and Hipp, various case reports have also appeared [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Among the cases included are rare cases featuring unusual clinical course, atypical pathological findings, involvement of genetic diseases and viral infection.…”
Section: Various Cases Of C1q Nephropathymentioning
confidence: 96%